FUNDAMENTAL RIGHTS IN CONFLICT WITH THE RIGHT TO BE FORGOTTEN DIGITALLY - Miñano Donayre, Alicia Liceth (2025)
Living in a globalized and hyper-digitally connected world has intensified the academic debate on the right to be forgotten and the emerging digital right to be forgotten, its regulation, limits, and the dilemmas it presents when confronted with the application of other fundamental rights. Currently, information can be observed circulating on the Internet about personal data of a diverse nature; however, the question arises when the information that circulates, despite being true, may violate the honor, reputation, or other fundamental rights of a person, colliding with the rights to information, expression, and freedom of the press. Furthermore, the so-called right to historical memory and collective identity introduces additional tensions, as does the societal participation required in the reintegration of convicted persons, in accordance with article VI of the Preliminary Title of Legislative Decree No. 654 – Criminal Execution Code. This work aims to carry out, through qualitative methodology, content analysis, legislative analysis, and jurisprudential examination, an integrated academic reflection that allows the proposal of a position favoring the coexistence of fundamental rights in conflict.